Value of a single-tube widal test in diagnosis of typhoid fever in Vietnam. - Parry, C; Hoa, N; Diep, T; Wain, J; Chinh, N; Vinh, H; Hien, T; White, N; Farrar, J (1999)
The diagnostic value of an acute-phase single-tube Widal test for suspected typhoid fever was evaluated with 2,000 Vietnamese patients admitted to an infectious disease referral hospital between 1993 and 1998. Test patients had suspected typhoid fever and a blood culture positive for Salmonella typhi (n= 1,400) or Salmonella paratyphi A (n = 45). Control patients had a febrile illness for which another cause was confirmed (malaria [n = 103], dengue [n = 76], or bacteremia due to another microorganism [n = 156] or tetanus (n = 265). An O-agglutinin titer of >/=100 was found in 18% of the febrile controls and 7% of the tetanus patients. Corresponding values for H agglutinins were 8 and 1%, respectively. The O-agglutinin titer was >/=100 in 83% of the blood culture-positive typhoid fever cases, and the H-agglutinin titer was >/=100 in 67%. The disease prevalence in investigated patients in this hospital was 30.8% (95% confidence interval, 26.8 to 35.1%); at this prevalence, an elevated level of H agglutinins gave better positive predictive values for typhoid fever than did O agglutinins. With a cutoff titer of >/=200 for O agglutinin or >/=100 for H agglutinin, the Widal test would diagnose correctly 74% of the blood culture-positive cases of typhoid fever. However, 14% of the positive results would be false-positive, and 10% of the negative results would be false-negative. The Widal test can be helpful in the laboratory diagnosis of typhoid fever in Vietnam if interpreted with care.